Socio-demographic factors and intimate partner violence as determinants of depression among female workers of University of Ibadan (2016)
Community based research on intimate partner violence against women using valid epidemiological methods both for descriptive and analytical studies has an important role in the planning for intervention against domestic violence. One of the weaknesses with previous studies is that they have used less specific diagnostic concepts for depressions and methodologies that is likely to underestimate intimate partner violence. Therefore, this study examined influence of demographic factors and interpersonal violence on depression among women at University of Ibadan, Nigeria. The study utilized survey design using random sampling technique across four selected Faculties of the University. Three hundred (300) women participated in the study yielding a return rate of 95%. Their ages ranged between 24 and 54 years with mean of 35.54 and standard deviation of 7.45. The instrument used was closed-ended questionnaire divided into three sections. This comprised of demographic variables, interpersonal violence and depression. Five hypotheses were tested. The result shows that younger participants reported less prevalence of depression than the older participants. Further, single workers reported significant lower score on depression than married and divorced workers. Additionally, female workers with school certificate and OND/NCE reported significantly higher score on depression than those with HND/Degree, Masters and Ph.D holders. There was no significant influence of religion on depression. Finally, inter-personal violence significantly predicted of depression. Based on the findings of the result, it was recommended that establishment of counselling units be included in the current federal service reforms being embarked upon. Also, the finding that interpersonal violence affects depression may encourage health professionals to identify groups of women at high risk of developing depression, and devise appropriate and effective measures or behavioural interventions to help abused women reduce their depression